Peningkatan Kemampuan Mahasiswa Dalam Memanajemen Referensi Ilmiah Melalui Pelatihan Mendeley - Icha Cahyaning Fitri; Rizki Apriliyanto; Abdul Jalil; Pio Tifar Ananda (Indonesian Journal Publisher, 2023)
Mendeley is a reference management software that helps organize scientific articles by creating references and bibliographies, and software users can also collaborate on social networks. This training aims to train students in citing articles, citations, and making a bibliography correctly. The methods in this activity are the registration stage, the implementation stage, and the evaluation stage. The Mendeley training activities went well, the participants enthusiastically participated in the training activities. Participants can create accounts, install, search references, make citations and create bibliography automatically. In addition, based on the pre-test and post-test data, the knowledge and skills of the participants increased, it was proven that the participants could use the Mendeley application well and could utilize the application to manage their scientific work references.